2006
DOI: 10.1152/physiolgenomics.00051.2005
|View full text |Cite
|
Sign up to set email alerts
|

Denervation in murine fast-twitch muscle: short-term physiological changes and temporal expression profiling

Abstract: Denervation deeply affects muscle structure and function, the alterations being different in slow and fast muscles. Because the effects of denervation on fast muscles are still controversial, and high-throughput studies on gene expression in denervated muscles are lacking, we studied gene expression during atrophy progression following denervation in mouse tibialis anterior (TA). The sciatic nerve was cut close to trochanter in adult CD1 mice. One, three, seven, and fourteen days after denervation, animals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 82 publications
7
78
2
Order By: Relevance
“…This number represents ϳ1% of the total number of probes present on the chip. Using gene ontology to classify these genes, based on molecular function, resulted in gene sets that represent a specific program of transcriptional changes that are largely similar to the well-studied programs of mammalian muscle atrophy (41,57). In addition, a number of new and unexpected genes, perhaps unique to the RBT wastage process, are reported here for the first time.…”
Section: Muscle Atrophy In Response To Vitellogenesismentioning
confidence: 83%
See 1 more Smart Citation
“…This number represents ϳ1% of the total number of probes present on the chip. Using gene ontology to classify these genes, based on molecular function, resulted in gene sets that represent a specific program of transcriptional changes that are largely similar to the well-studied programs of mammalian muscle atrophy (41,57). In addition, a number of new and unexpected genes, perhaps unique to the RBT wastage process, are reported here for the first time.…”
Section: Muscle Atrophy In Response To Vitellogenesismentioning
confidence: 83%
“…Glucose sparing in RBT may result from insulin resistance because of the prolonged energetic challenge from the reproductive demand. Reduced transcription of genes involved in glucose utilization is a common feature of muscle atrophy induced by fasting, the systemic diseases diabetes, cancer cachexia, and renal failure (41) and muscle disuse (57). Insulin resistance is a common feature of all forms of muscle degradation and is the direct trigger of accelerated muscle proteolysis (32,41).…”
Section: Genes Involved In Glucose Metabolismmentioning
confidence: 99%
“…Denervation of muscle (often with associated aberrant reinnervation) is regarded as a potent trigger to sarcopeniaboth associated with ageing and neuromuscular disordersand has recently been examined at the molecular level (Raffaello et al 2006). The use of IGF-I electroporation, recombinant human IGF-I and the peptide representing mechano-growth factor (MGF) have all been considered for ameliorating such neuromuscular conditions, including muscular dystrophy and motor neuron disease (Lynch 2004).…”
Section: Muscle Atrophy In Disuse Denervation and Medical Disordersmentioning
confidence: 99%
“…This is in line with previous studies that examined soleus and TA muscles in mice. 15,22 The deficit in absolute maximal force (À84%) was caused by both a reduced specific maximal force and a lower soleus muscle weight. We also observed that the effect of denervation was more severe for the soleus than the TA (À84% vs. À56% for absolute maximal force), confirming previous studies.…”
Section: Lt Had No Effect When Fully Functional Innervationmentioning
confidence: 99%